1997
DOI: 10.2527/1997.7592453x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding resistant starch affects fecal and cecal microflora and short-chain fatty acids in rats.

Abstract: The effects of different forms of resistant potato starch (RS) on the major microbial population groups and short-chain fatty acids (SCFA) in the cecum and feces of rats were studied over a 5-mo feeding period. Thirty 8-wk-old male Wistar rats, averaging 210 g initial body weight, were adapted for 7 d to a balanced basal diet containing 60% waxy maize starch devoid of any RS. On d 8, three groups of 10 rats each were fed diets containing the following forms of starch: 1) rapidly digestible waxy maize starch (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 34 publications
8
92
1
1
Order By: Relevance
“…22) Moreover, it has been shown that cecal contents have an abundance of intestinal bacteria and that this microflora producesglucosidases as well as -glucosidases. 23,24) Furthermore, Kometani et al have reported that G-hesperidin is hydrolyzed to hesperidin by -glucosidases, but that it can not undergo the action of -glucosidases. 10) On the basis of these findings, our observations suggest that orally administered G-hesperidin is initially hydrolyzed to hesperidin by small intestinal -glucosidases, and that released hesperidin is subsequently hydrolyzed to hesperetin by -glucosidases from intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…22) Moreover, it has been shown that cecal contents have an abundance of intestinal bacteria and that this microflora producesglucosidases as well as -glucosidases. 23,24) Furthermore, Kometani et al have reported that G-hesperidin is hydrolyzed to hesperidin by -glucosidases, but that it can not undergo the action of -glucosidases. 10) On the basis of these findings, our observations suggest that orally administered G-hesperidin is initially hydrolyzed to hesperidin by small intestinal -glucosidases, and that released hesperidin is subsequently hydrolyzed to hesperetin by -glucosidases from intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of starch affect the composition of fecal microflora and short-chain fatty acid production (6). Resistant starch is utilized by intestinal microflora (6) and seems to affect the cecal and colonic functions (7).…”
Section: Discussionmentioning
confidence: 99%
“…A range of human intestinal bacteria can ferment soluble starch; the most numerically dominant of these bacteria are members of the genera Bacteroides, Bifidobacterium, Fusobacterium, and Butyrivibrio (19). However, in animal models, inclusion of resistant starches in the diet has been shown to increase the population of bifidobacteria in the intestinal tract (4,5,16,25,29). Resistant starches have therefore also been proposed as potential prebiotics.…”
mentioning
confidence: 99%